The effect of physical preparation on the qualities of explosive power and transitional speed, and on the dribbling skills and accuracy of aiming football players in Algeria - Yassen, Abbasi (Arab Journal for Sciences and Research Publishing, 2017)
The researcher sought to find the relationship between physical preparation and some physical and technical characteristics of football players, where he used the experimental method As a method to study this subject and used physical and technical tests related to football and taken on a sample of nearly 14 players. The findings show that physical preparation has an effective and positive effect on transient velocity traits and explosive force. It also has an active role in the development of players technically, in improving the skills of evasion and accuracy of correction
Keywords: Physical preparation; Explosive power and speed; Dribbling skills and shooting accuracy; Football players